Pengaruh Model Learning Cycle 7E terhadap Kemampuan Literasi Sains Siswa Fase E di SMAN 8 Kota Jambi pada Materi Perubahan Iklim - Dea Putri Aryani; Ervan Johan Wicaksana; Desfaur Natalia (UNIB Press, 2026)
Scientific literacy is an essential competency that enables students to understand scientific concepts, solve problems, and make evidence-based decisions in response to the rapid development of science and technology. However, students' scientific literacy skills still need to be improved through the implementation of innovative learning models. This study aimed to analyze the effect of the Learning Cycle 7E model on the scientific literacy skills of Phase E students in biology learning on the topic of climate change at SMA Negeri 8 Kota Jambi. This study employed a quasi-experimental method using a nonequivalent control group design. Data were collected through a scientific literacy test that had met validity and reliability requirements and were analyzed using normality, homogeneity, linearity, homogeneity of regression, and Analysis of Covariance (ANCOVA) tests. The results showed that students in the experimental class achieved higher scientific literacy scores than those in the control class. ANCOVA analysis indicated that the Learning Cycle 7E model had a significant effect on scientific literacy skills of students (p = 0.019 < 0.05), with a Partial Eta Squared value of 0.079, indicating a medium effect size. Therefore, the Learning Cycle 7E model can be considered an effective alternative for improving students' scientific literacy in biology learning, particularly on the topic of climate change.